A Drivers Of Islamic Bond Liquidity In Malaysia: Latent Liquidity Approach - Rusmawati Said; Wan Nurhanan Wan Suhaimi; Norhuda Abd Rahim; Asmaddy Haris (Canadian Center of Science and Education, 2024)
International Journal of Economics and Finance; Vol. 10, No.10;2018